Upper GI biopsies for adenocarcinoma – how many biopsies should endoscopists take?. Issue 6 (1st April 2019) - Kaye, Philip; Lindsay, Daniel; Madhusudan, Srinivasan; Vohra, Ravinder; Catton, James; Platt, Craig; Ragunath, Krish
Abstract : Aims: There is evidence that four or five gastric cancer biopsies are required for accurate HER2 interpretation. However, the number of biopsies that need to be taken to reach this number of viable cancer biopsies is without evidence. This study aimed to address this gap by assessing the number of biopsies required to gain at least four viable biopsies containing cancer. Methods and results: A total of 105 consecutive biopsy cases of gastric and oesophageal adenocarcinoma were retrieved from files. Only definite cancer diagnoses were included; missed cancers or unproven cases were not considered. The cases were reviewed and the number of biopsies taken, and the number containing viable tumour was recorded. In total, 667 biopsies were taken, of which 471 had viable tumour (70.6%). Seventy of 105 cases (67%) had four viable tumour biopsies, but only 47 of 105 (45%) had five viable tumour biopsies. In order to have a >90% chance of having four viable tumour biopsies, seven needed to be taken, while 10 or more were required for a >90% chance of five viable tumour biopsies. Mathematically, using a 0.7 probability for a single biopsy, eight biopsies would be required for a 94% chance of at least four viable tumour biopsies. Conclusion: In our large upper GI cancer centre, many biopsy cases do not contain sufficient material for adequate HER2 assessment. In order to meet the four‐biopsy requirement for adequate HER2 assessment in >90% of cases, at least eight biopsies need to be taken, while 10 biopsies would be required for the 5‐cancer biopsy threshold.